The contents of an education Galichiny in the beginning of XX century (Pedagogy of Higher and Secondary Education, 2006)
In this article the author analyzed the content of an education tn Halychyna the XXth century. Also attention is drawn to its important and necessary usage tn the modem art school of Ukraine.
Keywords: art education; national art education; drawings; hand crafts; folk art